Approximation to studies on Peruvian soccer and communication: printed press, radio and television - Pahuacho Portella, Alonso Roberto (2018)
This article offers a journey through various texts –from the last fifty years of research– about the role and development of Peruvian soccer and its links with communication studies. The aim is to ponder the role played by sports media in the construction of Peruvian social reality, specifically in the case of football historiography in that country. Through a detailed review of three communication sources (written press, radio and television), we see a marked tendency from the Peruvian academy for the investigation of football and communications, taking as a source the written press and television, omitting the radio. Future research should also focus on visual aspects, new technologies and audiences.